2002
DOI: 10.1007/s00216-002-1344-5
|View full text |Cite
|
Sign up to set email alerts
|

Development of an FIA system with amperometric detection for determination of bentazone in estuarine waters

Abstract: On the basis of its electrochemical behaviour a new flowinjection analysis (FIA) method with ampero-metric detection has been developed for quantification of the herbicide bentazone (BTZ) in estuarine waters. Standard solutions and samples (200 L) were injected into a water carrier stream and both pH and ionic strength were automatically adjusted inside the manifold. Optimization of critical FIA conditions indicated that the best analytical results were obtained at an oxidation potential of 1.10 V, pH 4.5, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Electroanalytical techniques have been used for the determination of bentazone at different electrodes with or without surface modification [31,[86][87][88][89][90][91][92][93]. Overview of the electrochemical methods of analyses for bentazone determination is summarized in the Table 3.…”
Section: Electrochemical Detection Of Bentazonementioning
confidence: 99%
See 1 more Smart Citation
“…Electroanalytical techniques have been used for the determination of bentazone at different electrodes with or without surface modification [31,[86][87][88][89][90][91][92][93]. Overview of the electrochemical methods of analyses for bentazone determination is summarized in the Table 3.…”
Section: Electrochemical Detection Of Bentazonementioning
confidence: 99%
“…Similarly, an amperometric detection coupled to a flow injection analysis(FIA) system at a glassy carbon electrode has been proposed by Cerejeira et al [93]. Analysis of bentazone in estuarine waters was performed by means of calibration curves over the concentration range 2.50 to 50.0 µM at an oxidation potential of 1.10 V in acetate buffer solution (ABS) of pH 4.5.…”
Section: Electrochemical Detection Of Bentazonementioning
confidence: 99%
“…The toxicological studies have manifested that bentazone has been proved a highly toxic entity by dermal absorption and by ingestion in mammals (Harrison et al 2012). The reported studies have shown different toxicological effects of bentazone that include diarrhea, vomiting, weakness, trembling, eye, skin irritation and respiratory tract infections (Cerejeira et al 2002). The over doze of this harmful pesticide may cause renal failure, acute hepatitis and even demise (Liem et al 2011).…”
Section: Introductionmentioning
confidence: 99%